Quantitative Ultrasound Imaging Analysis of Anterior Talofibular Ligament in Adolescent Athletes with Chronic Ankle Instability - Sunjin Kim; Namwoong Kim; Jupil Ko (The Asian Journal of Kinesiology)
OBJECTIVES This study aimed to investigate the morphological changes in anterior talofibular ligament (ATFL) in adolescent athletes with chronic ankle instability (CAI). PARTICIPANTS A total of 40 adolescent athletes were included, divided into the CAI group (n = 20; age: 17.05 ± 0.75 years; height: 172.35 ± 8.98 cm; mass: 64.12 ± 12.51 kg) and the control group (n = 20; age: 16.50 ± 0.75 years; height: 174.35 ± 8.47 cm; mass: 64.83 ± 11.17 kg). Participants were categorized based on their history of ankle sprains and the criteria outlined by the International Ankle Consortium (IAC). METHODS Musculoskeletal ultrasound imaging was used to assess the thickness and length of the ATFL in both injured and uninjured ankles. RESULTS A significant increase in ATFL thickness was observed in the injured limbs of the CAI group compared to the control group (p = 0.007). CONCLUSIONS The ATFL in previously sprained ankles of adolescent athletes exhibited greater thickness compared to uninjured ankles. These findings align with similar observations in adult populations. Further research is warranted to explore the progression of CAI in adolescents and develop targeted management and treatment strategies.